DAMPAK PERKAWINAN DINI TERHADAP KESEJAHTERAAN KELUARGA (Studi di Desa Sendang Agung Kecamatan Plaosan Kabupaten Magetan) - Andika Budi Wicaksono; Ahmad Faruq (Kampus Akademik Publiser, 2024)
Marriage (marriage) is a very sacred thing, both according to religious teachings and its position in Marriage Law no. 1 of 1974 in article 1 states that